2013
DOI: 10.1111/jfb.12058
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent facial taste neurons of sea catfish Plotosusjaponicus: morphology and organization in the ganglion

Abstract: This study investigated the morphology of the recurrent facial taste neurons and their organization in the recurrent ganglion of the sea catfish Plotosus japonicus. The recurrent ganglion is independent of the anterior ganglion, which consists of trigeminal, facial and anterior lateral line neurons that send peripheral fibres to the head region. The recurrent taste neurons are round or oval and bipolar, with thick peripheral and thin central fibres, and completely wrapped by membranous layers of satellite cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The Japanese sea catfish, P. japonicus , has been utilized in numerous studies on gustatory capabilities in teleost fish [Kiyohara et al, 1986Marui et al, 1988;Sakata et al, 2001;Denil et al, 2013;Caprio et al, 2014Caprio et al, , 2015. Here, we used whole-mount immunohistochemistry to characterize the morphology and innervation of the external and intraoral taste buds of this interesting species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Japanese sea catfish, P. japonicus , has been utilized in numerous studies on gustatory capabilities in teleost fish [Kiyohara et al, 1986Marui et al, 1988;Sakata et al, 2001;Denil et al, 2013;Caprio et al, 2014Caprio et al, , 2015. Here, we used whole-mount immunohistochemistry to characterize the morphology and innervation of the external and intraoral taste buds of this interesting species.…”
Section: Discussionmentioning
confidence: 99%
“…The gustatory system of the Japanese sea catfish, Plotosus japonicus , has been examined in many studies [Kiyohara et al, 1986Marui et al, 1988;Sakata et al, 2001;Denil et al, 2013]. A recent study showed that P. japonicus could sense decreases of ≤ 0.1 pH unit in environmental seawater, associated with the increase of H + / CO 2 from the respiration of prey, and utilized this ability to detect the prey [Caprio et al, 2014].…”
mentioning
confidence: 99%